The density of tobacco retailers in home and school environments and relationship with adolescent smoking behaviours in Scotland. Issue 1 (4th November 2014) - Shortt, N K; Tisch, C; Pearce, J; Richardson, E A; Mitchell, R
Abstract : Background: Neighbourhood retailing of tobacco products has been implicated in affecting smoking prevalence rates. Long-term smoking usually begins in adolescence and tobacco control strategies have often focused on regulating 'child spaces', such as areas in proximity to schools. This cross-sectional study examines the association between adolescent smoking behaviour and tobacco retail outlet density around home and school environments in Scotland. Methods: Data detailing the geographic location of every outlet registered to sell tobacco products in Scotland were acquired from the Scottish Tobacco Retailers Register and used to create a retail outlet density measure for every postcode. This measure was joined to individual responses of the Scottish Schools Adolescent Lifestyle and Substance Use Survey (n=20 446). Using logistic regression models, we explored the association between the density of retailers, around both home and school address, and smoking behaviours. Results: Those living in the areas of highest density of retailers around the home environment had 53% higher odds of reporting having ever smoked (95% CI 1.27 to 1.85, p<0.001) and 47% higher odds of reporting current smoking (95% CI 1.13 to 1.91 p<0.01). Conversely, those attending schools in areas of highest retail density had lower odds of having ever smoked (OR 0.66, 95% CI 0.50 to 0.86 p<0.01) and lower odds of current smoking (OR 0.75, 95% CI 0.59 to 0.95, p<0.05). Conclusions: The density of tobacco retail outlets in residential neighbourhoods is associated with increased odds of both ever smoked and current smoking among adolescents in Scotland. Policymakers may be advised to focus on reducing the overall density of tobacco outlets, rather than concentrating on 'child spaces'.